Selected prose works Commentary on Genesis, Commentary on Exodus, Homily on our Lord, Letter to Publius/ St. Ephrem the Syrian. Transl. by Edward G. Mathews, Jr. and Joseph P. Amar. Ed. by Kathleen McVey - Ephraem Syrus 306-373; Mathews, Edward G. 1954-; Amar, Joseph P. 1946-; McVey, Kathleen E. 1944-; Ephraem Syrus 306-373 (Washington, D.C Catholic Univ. of America Press, 1994)
Commentary on Genesis -- Commentary on Exodus -- Homily on our Lord -- Letter to Publius
Commentary on Genesis -- Commentary on Exodus -- Homily on our Lord -- Letter to Publius
Includes bibliographical references (p. xv-xxx) and indexes
In syr. Sprache
Keywords: Jesus Christ -- Person and offices -- Sermons -- Early works to 1800; Bible -- Commentaries -- Early works to 1800; Bible -- Commentaries -- Early works to 1800; Spiritual Life -- Christianity -- Early works to 1800